Managing talent at Lupin Limited (A) - Sharda, Kirti (London : Indian Institute of Management, Ahmedabad, 2011)
Lupin, a transnational pharmaceutical company, had put in place a talent management process to ensure achievement of its ambitious organisational goals. The company was successful in creating acceptance for talent management within the organisation. But a few challenges persisted, most critical of them being: how do you manage talent in a high-growth industry that is insular and domain-focused, without jeopardising the relationship-oriented culture and hierarchical structure of the organisation? The case encourages participants to think about the issues faced by Lupin in the design and implementation of its talent management goals and possible action plans to meet these challenges.
Originally published in Sharda, K. (2011). Managing talent at Lupin limited (A). OB0209(A). Indian Institute of Management, Ahmedabad.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Lupin Limited; Manpower planning; Goal setting in personnel management